A comparative study between the administration of preoperative intravenous tranexamic acid and those with 24-hour postoperative continuation for reduction of blood loss in degenerative lumbar spinal stenosis surgery - Malairungsakul, Anan (Biomedical Sciences and Clinical Medicine, 2024)
Purpose of the study is to compare the effectiveness of administration of tranexamic acid for reduction of blood loss and blood transfusion on lumbar spine surgery. Hundred patients was divided equally and received tranexamic acid 10 mg/kg body weight in single bolus dose before surgery,comparing with those who recieved single bolus dose with continuous 24 hrs post operatively after surgury. Blood loss during the operation and postoperation was recorded, as well as blood hemoglobin concentration and hematocrit, operation time, transfusion of blood products. The postoperative blood loss was reduced significantly in single bolus dose with continuous post operative 24hrs as compared to single bolus dose 717.80±313.75 mL vs 606.70±209.19 mL (p <0.05). The number of blood transfusion was 10 cases in single bolus dose with continuous post operative 24 hrs as compared to 16 cases in single bolus dose. There were no significant difference in total blood loss intra operative blood loss, hemoglobin and hematocrit.